Prevalence of Human Malaria Parasite among Pregnant Women Attending Antenatal Care at Eldin Specialist Hospital Jos, Plateau State, Nigeria - Nanvyat, Nannim; Jwat, N. D.; Luka, I.; Otakpa, E. O.; Mamka’a, T. T.; Samson, M.; Goselle, O. N.; Mwansat, G. S. (Sahel Journal of Life Sciences FUDMA, 2024)
Malaria infection is a severe parasitic infectious disease transmitted by the bite of an infected female Anopheles mosquito. The disease presents with severe consequences in pregnant women and children <5 years, particularly in sub-Saharan Africa where the burden of the disease is highest. Malaria in pregnancy may present with severe symptoms such as miscarriages, premature delivery, low-birth-weight neonates, and neonatal death. This study therefore determined the prevalence of malaria infection among pregnant women in Jos Metropolis. Capillary blood samples were collected from 200 symptomatic pregnant women attending Eldin Specialist Hospital, in Jos, and thin and thick blood Giemsa-stained films were prepared and examined for the presence of malaria parasites. Our findings revealed that 70(35%) of the 200 pregnant women sampled were infected. Based on gravidity, incidence of malaria infection was highest in the primigravidae 45 (41.9%) as compared to multigravidae 25 (27.8%) although decreasing with gestational age, as subjects in their first trimester were more infected 44 (44.0%) with the least being those in their third trimester14 (21.5%). Two peaks of infection were encountered in respect to age; 46.2% in subjects aged 20-24 years and 42.9% in subjects aged 30-39 years with the least infection recorded in subjects aged > 39 years, 17.9%. Malaria incidence is decreasing in the country due to scale up intervention and prevention measures, however, malaria still remains a major public health problem among pregnant women and deliberate efforts need to be put in place to forestall the negative impact of this disease.